South Arabia’s prehistoric monument landscape shows social resilience to climate change - Joy McCorriston; Lawrence Ball; Michael J. Harrower; Ian M. Hamilton; Sarah J. Ivory; Matthew J. Senn; Tara Steimer-Herbet; Abigail F. Buffington; Ali Ahmad Al-Kathiri; Ali Musalam Al-Mahri (PLoS ONE, 2025)
In arid regions across northern Africa, Asia and Arabia, ancient pastoralists constructed small-scale stone monuments of varying form, construction, placement, age, and function. Classification studies of each type have inhibited a broader model of their collective and enduring role within desert socio-ecosystems. Our multivariate analysis of 371 archaeological monuments in the arid Dhofar region of Oman identifies environmental and cultural factors that influenced variable placement and construction across a 7000-year history. Our results show that earlier monuments were built by larger, concurrent groups during the Holocene Humid Period (10,000–6000 cal BP). With increasing aridification, smaller groups constructed monuments and eventually switched to building them in repetitive visits. Our model emphasizes the core role of monuments as a flexible technology in social resilience among desert pastoralists.